The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1123/jab.28.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Leg Tissue Mass Composition Affects Tibial Acceleration Response Following Impact

Abstract: To date, there has not been a direct examination of the effect that tissue composition (lean mass/muscle, fat mass, bone mineral content) differences between males and females has on how the tibia responds to impacts similar to those seen during running. To evaluate this, controlled heel impacts were imparted to 36 participants (6 M and 6 F in each of low, medium and high percent body fat [BF] groups) using a human pendulum. A skin-mounted accelerometer medial to the tibial tuberosity was used to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The first set of three trials was applied using a human pendulum (Duquette & Andrews, 2010;Flynn, Holmes, & Andrews, 2004;Lafortune & Lake, 1995;Schinkel-Ivy et al, 2012), with participants securely strapped supine to the pendulum, and the right knee joint space aligned with the leading edge of the pendulum frame. The pendulum was manually pulled back a distance (between 50 and 65 cm) in order to achieve a velocity (linear voltage differential transformer attached to the pendulum; Celesco DV301, Don Mills, ON, Canada) of 1.0-1.15 m · s -1 and a force of 1.8-2.8 times body weight (Cavanagh & Lafortune, 1980;Duquette & Andrews, 2010;Flynn et al, 2004;Holmes & Andrews, 2006; Schinkel-Ivy, Burkhart, & Andrews, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first set of three trials was applied using a human pendulum (Duquette & Andrews, 2010;Flynn, Holmes, & Andrews, 2004;Lafortune & Lake, 1995;Schinkel-Ivy et al, 2012), with participants securely strapped supine to the pendulum, and the right knee joint space aligned with the leading edge of the pendulum frame. The pendulum was manually pulled back a distance (between 50 and 65 cm) in order to achieve a velocity (linear voltage differential transformer attached to the pendulum; Celesco DV301, Don Mills, ON, Canada) of 1.0-1.15 m · s -1 and a force of 1.8-2.8 times body weight (Cavanagh & Lafortune, 1980;Duquette & Andrews, 2010;Flynn et al, 2004;Holmes & Andrews, 2006; Schinkel-Ivy, Burkhart, & Andrews, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…However, Burkhart, Schinkel-Ivy, and Andrews (2013) identified a relationship between the soft tissue composition of the distal lower extremity and the development of lower extremity injuries in basketball, soccer and track and field athletes. In addition, Schinkel-Ivy et al (2012) found that the peak shock (measured as acceleration) at the tibial tuberosity was significantly affected by the mass of the tissues located in the distal lower extremity. Pain and Challis (2002) suggested that ignoring the role of soft tissue motion may limit our understanding of injury prevention strategies.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in comparison with rigid body models (representing bone) and wobbling mass models (representing rigid and soft tissues), the latter substantially reduced both external and internal loading (Gruber et al 1998;Liu and Nigg 2000;Pain and Challis 2001Gittoes et al 2006). Furthermore, Schinkel-Ivy et al (2012) found that greater shank tissue masses, specifically lean mass and bone mineral content, contributed to decreased acceleration responses measured at the proximal tibia following impact.…”
Section: Introductionmentioning
confidence: 93%
“…A human pendulum (, 13 kg; Flynn et al 2004;Holmes and Andrews 2006;Andrews 2010a, 2010b;Schinkel-Ivy et al 2012) was used to swing the participant towards a rigid impact apparatus. The participant was positioned supine on the pendulum with the left leg in full extension (knee joint line situated at the leading edge of the pendulum).…”
Section: Equipment and Instrumentationmentioning
confidence: 99%